H7N7 viral infection elicits pronounced, sex-specific neuroinflammatory responses in vitro - Gabele, Lea; Bochow, Isabell; Rieke, Nele; Sieben, Christian; Michaelsen-Preusse, Kristin; Hosseini, Shirin; Korte, Martin (Frontiers in Cellular Neuroscience, 2024)
Influenza A virus (IAV) infection can increase the risk of neuroinflammation, and subsequent neurodegenerative diseases. Certain IAV strains, such as avian H7N7 subtype, possess neurotropic properties, enabling them to directly invade the brain parenchyma and infect neurons and glia cells. Host sex significantly influences the severity of IAV infections. Studies indicate that females of the reproductive age exhibit stronger innate and adaptive immune responses to IAVs compared to males. This heightened immune response correlates with increased morbidity and mortality, and potential neuronal damage in females. Understanding the sex-specific neurotropism of IAV and associated mechanisms leading to adverse neurological outcomes is essential. Our study reveals that primary hippocampal cultures from female mice show heightened interferon-β and pro-inflammatory chemokine secretion following neurotropic IAV infection. We observed sexspecific differences in microglia activation: both sexes showed a transition into a hyper-ramified state, but only male-derived microglia exhibited an increase in amoeboid-shaped cells. These disparities extended to alterations in neuronal morphology. Neurons from female mice displayed increased spine density within 24 hours post-infection, while no significant change was observed in male cultures. This aligns with sex-specific differences in microglial synaptic pruning. Data suggest that amoeboid-shaped microglia preferentially target postsynaptic terminals, potentially reducing neuronal hyperexcitability. Conversely, hyper-ramified microglia may focus on presynaptic terminals, potentially limiting viral spread. In conclusion, our findings underscore the utility of primary hippocampal cultures, incorporating microglia, as an effective model to study sex-specific, virus-induced effects on brain-resident cells.